2016
DOI: 10.1007/s00429-016-1201-5
|View full text |Cite
|
Sign up to set email alerts
|

Anatomic characterization of prelemniscal radiations by probabilistic tractography: implications in Parkinson’s disease

Abstract: To characterize the anatomical connectivity of the prelemniscal radiations (Raprl), a white matter region within the posterior subthalamic area (PSA) that is an effective neurosurgical target for treating motor symptoms of Parkinson's disease (PD). Diffusion-weighted images were acquired from twelve healthy subjects using a 3T scanner. Constrained spherical deconvolution, a method that allows the distinction of crossing fibers within a voxel, was used to compute track-density images with sufficient resolution … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 68 publications
1
23
0
1
Order By: Relevance
“…On the other hand, with probabilistic tractography, evidenced in our DWI-MRI studies, we have identified a subset of cerebellar-thalamic fibers ending anteriorly over the ventralis oralis posterior nucleus (Vop), as described in other studies [6] (Fig. 1a), overlapping a fiber component connecting Gp with the thalamus [2, 3]. These fibers have been described in anatomical studies as well; arriving at the thalamus in the thalamic fasciculus [7], the fibers connect the Vop with the supplementary motor area and the dorsolateral frontal cortex.…”
Section: Introductionsupporting
confidence: 73%
See 1 more Smart Citation
“…On the other hand, with probabilistic tractography, evidenced in our DWI-MRI studies, we have identified a subset of cerebellar-thalamic fibers ending anteriorly over the ventralis oralis posterior nucleus (Vop), as described in other studies [6] (Fig. 1a), overlapping a fiber component connecting Gp with the thalamus [2, 3]. These fibers have been described in anatomical studies as well; arriving at the thalamus in the thalamic fasciculus [7], the fibers connect the Vop with the supplementary motor area and the dorsolateral frontal cortex.…”
Section: Introductionsupporting
confidence: 73%
“…In previous reports, we described the fiber composition of prelemniscal radiations (Raprl) in Parkinson disease (PD) patients [1, 2] and age- and sex-paired controls [3], evaluated through high-angular-resolution diffusion-weighted imaging (DWI) using magnetic resonance imaging (MRI). In the studied cases, 3 fiber components were identified: cerebellar-thalamic-cortical fibers, globus pallidus (Gp)-pedunculopontine fibers, and frontal orbitofrontal cortex-mesencephalic tegmental fibers.…”
Section: Introductionmentioning
confidence: 99%
“…We have previously reported that suboptimum outcome results when DBS leads to selective improvement of only one PD symptom. This may be considered as indirect evidence that different symptoms are mediated by different anatomical circuits involving the Raprl .…”
Section: Discussionmentioning
confidence: 99%
“…The fiber composition of Raprl may explain the effect of DBS on different PD symptoms. Three components have been demonstrated in a cohort of PD patients and control healthy individuals paired in age and sex . The cerebellar‐thalamic cortical component links the cerebellum with the primary motor cortex (PMC) through Vim projections, while a different fiber subset links the supplementary motor area (SMA) through the ventral lateral (Vop) thalamic nucleus; this subset of fibers overlaps the projections of Gpi to the thalamus.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation